(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In order to improve the finishing effect of raw bamboo fiber treated with sericin protein, it was selectively oxidized by NaIO4 and then treated with sericin solution. The morphology and structure of sericin proteinic raw bamboo fiber were analyzed by means of SEM, XRD, TG and DSC. The treatment results show that sericin protein could be directly coated onto the oxidized raw bamboo fiber without any other reagent and a covalence was formed between amido and aldehyde group. After being treated with sericin protein solution, the thermal stability and crystallinity of the oxidized raw bamboo fiber improved and the surface became smoother.